Removal of Cu Metals from Wastewater by Adsorption using Synthetic Zeolites from Rice Husk and Corncob - Imas Solihat; Lilis Sulistiawaty; Putri Hawa Syaifie; Agus Taufiq (Universitas Jenderal Soedirman, 2020)
Heavy metals, such as Cu, are hazardous components so that it needs to reduce their concentration due to their negative impact on the environment. One method that can be used to reduce heavy metals in waste is to use adsorbents (synthetic zeolites). Utilization of agricultural waste such as rice husks and corncobs as precursors of synthetic zeolites will add economic value because it is relatively cheap with a lot of availability. This research aimed to find out new variants of synthetic zeolites, which can reduce the concentration of Cu in the adsorption process. The study consisted of 3 stages, the first stage was zeolite synthesis by the sol-gel method with 3 zeolite variants (A, B and C), the second stage was characterization using XRD and SEM, and the third stage was zeolites optimization (variations in pH, weight, and concentration). According to the results of SEM, zeolite B had a larger and uniform pore size so as it produced a greater adsorption capacity (4.82 mg/g) to be compared with zeolites A and C. The results showed synthetic zeolite C was able to adsorb Cu waste by following the adsorption isotherm model of Langmuir